2012
DOI: 10.1161/circulationaha.111.053405
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Klotho Deficiency Potentiates the Development of Human Artery Calcification and Mediates Resistance to Fibroblast Growth Factor 23

Abstract: Background-Klotho is known to function as a cofactor for the phosphatonin, fibroblast growth factor (FGF)-23 at the kidney.FGF-23 levels rise in chronic kidney disease (CKD) despite progression of accelerated vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
393
6
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(439 citation statements)
references
References 57 publications
(67 reference statements)
29
393
6
11
Order By: Relevance
“…It remains unknown how far circulating sKlotho levels reflect tissue Klotho expression. In the context of controversial data on Klotho expression in vascular cells (21,22,30), we cannot rule out that Klotho tissue expression-unlike plasma sKlotho-may be associated with cardiovascular outcome. Nonetheless, following most recent animal data, which argue against Klotho expression in vascular cells (30), most experts believe that Klotho tissue expression is largely confined to kidney and parathyroidal cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It remains unknown how far circulating sKlotho levels reflect tissue Klotho expression. In the context of controversial data on Klotho expression in vascular cells (21,22,30), we cannot rule out that Klotho tissue expression-unlike plasma sKlotho-may be associated with cardiovascular outcome. Nonetheless, following most recent animal data, which argue against Klotho expression in vascular cells (30), most experts believe that Klotho tissue expression is largely confined to kidney and parathyroidal cells.…”
Section: Discussionmentioning
confidence: 93%
“…More direct evidence for a beneficial cardiovascular role of sKlotho derives from rodent CKD models, in which sKlotho lowered active phosphate uptake by vascular smooth muscle cells and thus protected animals against vascular calcification (21). Similarly, in human aortic smooth muscle cells, uremic serum downregulated Klotho gene expression and induced calcifying pathways, whereas restoration of Klotho activity protected against extracellular calcium deposition (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that, in the absence of klotho, increased FGF23 levels exert pro-calcific effects via non-specific low affinity binding to its receptors [17]. A recent study showed that in human arteries, restoration of klotho expression by vitamin D receptor activators could unmask anticalcific effect of FGF23 [18]. These data, even if showing a strong and independent association between FGF23, CVD and hard end points throughout different stages of CKD, are still insufficient to determine the nature of FGF23 as a biomarker or as an effector in vascular calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that not only FGFR1, but also FGFR3 is expressed in human vascular tissue (Donate-Correa et al, 2011; Lim et al, 2012). Furthermore, it has demonstrated that expression of FGFR1 and FGFR3 in human arteries from healthy individuals and CKD patients is critical for vascular calcification, and that the physical association of Klotho, FGFR1 and FGFR3 is an essential mechanism to prevent critical vascular calcification (Lim et al, 2012). …”
Section: Discussionmentioning
confidence: 99%